The Close Relationship between Large Bowel and Heart: When a Colonic Perforation Mimics an Acute Myocardial Infarction - Maria Francesca Secchi; Carlo Torre; Giovanni Dui; Francesco Virdis; Mauro Podda (Case Reports in Surgery)
Colonoscopic perforation is a serious and potentially life-threatening complication of colonoscopy. Its incidence varies in frequency from 0.016% to 0.21% for diagnostic procedures, but may be seen in up to 5% of therapeutic colonoscopies. In case of extraperitoneal perforation, atypical signs and symptoms may develop. The aim of this report is to raise the awareness on the likelihood of rare clinical features of colonoscopic perforation. A 72-year-old male patient with a past medical history of myocardial infarction presented to the emergency department four hours after a screening colonoscopy with polypectomy, complaining of neck pain, retrosternal oppressive chest pain, dyspnea, and rhinolalia. Right chest wall and cervical subcutaneous emphysema, pneumomediastinum, pneumoretroperitoneum, and bilateral subdiaphragmatic free air were reported on the chest and abdominal X-rays. The patient was treated conservatively, with absolute bowel rest, total parental nutrition, and broad-spectrum intravenous antibiotics. Awareness of the potentially unusual clinical manifestations of retroperitoneal perforation following colonoscopy is crucial for the correct diagnosis and prompt management of colonoscopic perforation. Conservative treatment may be appropriate in patients with a properly prepared bowel, hemodynamic stability, and no evidence of peritonitis. Surgical treatment should be considered when abdominal or chest pain worsens, and when a systemic inflammatory response arises during the conservative treatment period.